Associations between the HDL-C/ApoA-I ratio and fasting glucose levels differ by glucose deciles, HDL-C/ApoA-I ratio ranges and sex - Zhang, Yuetao; Wang, Yue (Diabetes research and clinical practice, 2022)
To learn how high-density lipoprotein cholesterol (HDL-C) and apolipoprotein A-I (ApoA-I) are associated with fasting blood glucose (FBG). A cross-sectional study was performed in 97,801 males and 70,773 females without known disease. The ratio of HDL-C/ApoA-I is more stable for predicting fasting glucose levels than HDL-C or ApoA-I alone. In subjects with HDL-C/ApoA-I ≤ 0.9, HDL-C/ApoA-I ratios were negatively associated with FBG levels, with similar patterns between sexes, and the associations gradually strengthened along with the deciles of FBG increase. In subjects with HDL-C/ApoA-I > 0.9, FBG remained at relatively lower levels in both sexes, while the associations between the FBG level and the HDL-C/ApoA-I ratio turned from negative in the lowest five deciles to positive in the highest two deciles of FBG levels in males. Adjustment for known confounders only slightly attenuated the above association patterns. Subpopulations with HDL-C/ApoA-I ≤ 0.9 were distributed in the higher ranges of triglyceride (TG), non-HDL-C, total cholesterol (TC) and ApoA-I levels and lower ranges of HDL-C levels. The HDL-C/ApoA-I ratio sorted TG, non-HDL-C, TC, ApoA-I and HDL-C levels and hence might combine more coordinating metabolic characteristics of these lipids in association with blood glucose homeostasis.